2016
DOI: 10.1515/acph-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the topical spray containing Centella asiatica extract and its efficacy on excision wounds in rats

Abstract: Centella asiatica was extracted by methanol. The assay content of triterpenes in the extract was 0.12 % asiatic acid, 0.54 % madecassic acid, 0.25 % asiaticoside and 1.02 % madecassoside. The extract was complexed with hydroxypropyl-b-cyclodextrin (HP-b-CD) and formulated with Eudragit E100, glycerol, PEG 400, copovidone, ethanol and purified water. A clear yellowish solution (F1-F8) was obtained. The formulations had a pH of 5.5-6.0 with viscosity in the range of 20-60 mPa s, surface tension 20.3-24.6 mN m -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…The healing process depends on the biosynthesis and deposition of collagen and its maturation [36]. Our results showed that both EO treatments had the better structure of scar tissue and a greater deposit of collagen.…”
Section: Discussionmentioning
confidence: 56%
“…The healing process depends on the biosynthesis and deposition of collagen and its maturation [36]. Our results showed that both EO treatments had the better structure of scar tissue and a greater deposit of collagen.…”
Section: Discussionmentioning
confidence: 56%
“…The C. asiatica extract and its triterpenoids had certain therapeutic and relieving effects on acne, baldness, vitiligo, atopic dermatitis, and wounds (Sawatdee et al, 2016;Choi et al, 2017;Ling et al, 2017;Ju Ho et al, 2018;Shen et al, 2019) (Table 4).…”
Section: Effects On Skin Diseasesmentioning
confidence: 99%
“…Several studies demonstrated the effect of C. asiatica in wound healing when topically applied (Gohil et al, ; Gul Satar et al, ; Hong et al, ; Sawatdee, Choochuay, Chanthorn, & Srichana, ). Its mechanism of action has been attributed to increase cellular proliferation and collagen synthesis at the wound site (Pazyar et al, ; Sunilkumar, Parameshwaraiah, & Shivakumar, ), increase in angiogenesis (Incandela et al, ; Rosen, Blumenthal, & McCallum, ), and it has an effect on keratinization, which aids in thickening skin in areas of infection (Poizot & Dumez, ).…”
Section: Centella Asiaticamentioning
confidence: 99%
“…Commercial enzymatic debriding agents are available, and some previous studies reported their efficacy mainly in the treatment of burn wounds (Cordts et al, 2016;Rosenberg et al, 2014;Schulz et al, 2017) and to clear bruises and hematomas on boxers (Blonstein, Bromelain (Dutta & Bhattacharyya, 2013;Ali et al, 2015;Praveen et al, 2014;Manosroi et al, 2014;Ataide, de Carvalho, et al, 2017;Ekambaram et al, 2017) (Dutta & Bhattacharyya, 2013;Hu et al, 2011;Singer et al, 2010;Wu et al, 2012) (Blonstein, 1960;Cordts et al, 2016;Koller et al, 2008;Krieger et al, 2012;Rosenberg et al, 2004;Rosenberg et al, 2014;Schulz et al, 2017) Propolis ( Centella asiatica (Hong et al, 2005;Shukla, Rasik, Jain, et al, 1999;Gohil et al, 2010;Incandela et al, 2001;Zhang et al, 2016) (Shukla, Rasik, Jain, et al, 1999;Sawatdee et al, 2016;Gohil et al, 2010;Gul Satar et al, 2013;Sunilkumar et al, 1998;Rosen et al, 1967;Incandela et al, 2001;Poizot & Dumez, 1978;Suguna et al, 1996;Zhang et al, 2016) …”
Section: Bromelainmentioning
confidence: 99%